Depression and burnout in (junior) elite athletes: Reviewing the state of knowledge and analysing their relationship - Nixdorf, R. (Technische Universität München, 2018)
1 Psychological disorders in elite sports 1.1 Depression in elite sports 1.2 Burnout in elite sports 1.3 Depression and burnout in elite sports 1.3.1 Relation of syndromes 1.3.2 Relation of concepts and factors 1.4 Research potential 1.5 Aim of the studies 2 Methods 2.1 Study 1: Systematic literature review 2.2 Research project 2.3 Study 2: Relating burnout and depression 3 Studies 3.1 Study 1: Depression among elite athletes 3.2 Study 2: Burnout and depression in junior elite athletes. 4 Discussion 4.1 Depression in elite athletes. 4.2 Burnout and depression 4.3 Conclusion